Femoral Head Growth Plate Dysplasia and Fracture in Juvenile Rabbits Induced by Off-target Antiangiogenic Treatment. (August 2016) - Hall, A. Peter; Mitchard, T.; Rolf, M. G.; Stewart, J.; Duffy, P.
Epiphyseal growth plate dysplasia (chondrodysplasia) might be considered as the pathognomonic feature of antiangiogenic treatment in preclinical species as it is reliably and dose-responsively induced in rodents and monkeys with vascular endothelial growth factor receptor (VEGFR) inhibitors, fibroblast growth factor (FGF) receptor inhibitors, matrix metalloproteinase inhibitors, and vascular targeting agents. Here we report epiphyseal growth plate dysplasia in juvenile rabbits treated with an oral spleen tyrosine kinase inhibitor induced by off-target antiangiogenic inhibition of VEGF and FGF family kinase receptors. Epiphyseal growth plate dysplasia resulted in weakening and fracturing of the femoral head physis in 6 of 10 male and 1 of 10 female animals as well as microfracturing and dysplasia of the distal femoral articular cartilage in 1 male animal. Fracture lines ran through the zone of hypertrophic cartilage (as well as adjacent zones), were orientated parallel to the physeal plane, and often involved displacement of the femoral head. We would suggest that the high prevalence of growth plate fracture in the rabbit may represent a potential additional adverse risk to those already established for children treated with antiangiogenic therapy.